2020
DOI: 10.1055/s-0039-1697988
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cervical Vestibular-Evoked Myogenic Potentials in Adults with Moderate to Profound Sensorineural Hearing Loss: A Preliminary Study

Abstract: Introduction The cochlea and the vestibular receptors are closely related in terms of anatomy and phylogeny. Patients with moderate to profound sensorineural hearing loss (MPSHL) should have their vestibular organ functions tested. Objective To evaluate the incidence of vestibular abnormalities in patients with MPSHL and to study the correlation between the etiology of hearing loss (HL) and a possible damage to the labyrinth. Methods A case-control retrospective study was performed. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For patients who suffer from hearing loss after an episode of SSNHL, cochlear implantation may be the only opportunity, due to the possible ossification of the cochlea-especially after viral infections [20][21][22][23]. As far as diagnostics of moderate to profound sensorineural hearing loss (MPSHL), the use of cVEMPs (cervical vestibular-evoked myogenic potentials) to identify and intervene promptly in cases of vestibular disorders, which could endanger the process of integration of the critical sensory stimuli for correct posture and locomotion [24,25]. Additionally, the evidence for viral involvement in SSNHL, Ménière's disease, and vestibular neuritis is indirect and equivocal [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who suffer from hearing loss after an episode of SSNHL, cochlear implantation may be the only opportunity, due to the possible ossification of the cochlea-especially after viral infections [20][21][22][23]. As far as diagnostics of moderate to profound sensorineural hearing loss (MPSHL), the use of cVEMPs (cervical vestibular-evoked myogenic potentials) to identify and intervene promptly in cases of vestibular disorders, which could endanger the process of integration of the critical sensory stimuli for correct posture and locomotion [24,25]. Additionally, the evidence for viral involvement in SSNHL, Ménière's disease, and vestibular neuritis is indirect and equivocal [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the health claim code database, laboratory findings, such as pulmonary function tests and vestibular function tests, were not available. The difficulty of diagnosis of Ménière’s disease could have originated from the combined cochleovestibular dysfunction in as high as 71.5% of moderate to profound sensorineural hearing loss patients [ 43 ]. In addition, anatomical variation could trigger Menieriform syndrome [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNHL has been associated with ERS in animal studies [ 6 8 ] and ERS may serve as an indicator of vascular or nerve damage [ 2 ]. To date, however, there are no reports in the literature about the role of ERS in SSNHL, probably because of the inability to obtain tissue samples from the inner ear of patients at the onset of SSNHL, and the lack of reliable SSNHL animal models.…”
Section: Discussionmentioning
confidence: 99%
“…It primarily presents as acute hearing loss, tinnitus, and dizziness requiring urgent care by an otorhinolaryngologist [ 1 ]. Some previous data suggested that SSNHL could be idiopathic, or originate from other diseases, such as vascular, infectious, or otologic conditions [ 1 , 2 ]. SSNHL is primarily treated with glucocorticoids (GCs) such as dexamethasone and methylprednisolone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation